The benzodiazepines : from molecular biology to clinical practice - Costa, Erminio, 1924-2009 (New York (N.Y.) : Raven Press, 1983)
Onderwerp van dit boek zijn de benzodiazepines, de medicijnen die gebruikt worden om mensen van hun angst af te helpen.
Keywords: Benzodiazepines -- Congresses; Benzodiazepines; Mental disorders -- Drug therapy